2021
DOI: 10.1155/2021/3632576
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of PIK3CA as a Marker Associated with Prognosis and Immune Infiltration in Renal Clear Cell Carcinoma

Abstract: Background. Kidney renal clear cell carcinoma (KIRC) is the most prevalent renal malignancy. The therapeutic strategies for advanced KIRC are very few, with only sunitinib being widely approved. Mutations in the PIK3CA gene can affect tumor cell proliferation, metastasis, and patients’ survival. Methods. Bioinformatics analysis was performed to explore the expression and clinical significance of PIK3CA in KIRC. Moreover, qRT-PCR was conducted to verify the result. Results. Subgroup analyses of KIRC tissue base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…According to reports, the common pathways activated in KIRC are PI3K/AKT/mTOR, VHL/HIF-1α, and JAK/STAT ( 42 44 ). KIRC is characterized by controlling hypoxic signaling pathways, leading to metabolic dysregulation, promoting neovascularization, and creating a microenvironment conducive to tumor growth ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to reports, the common pathways activated in KIRC are PI3K/AKT/mTOR, VHL/HIF-1α, and JAK/STAT ( 42 44 ). KIRC is characterized by controlling hypoxic signaling pathways, leading to metabolic dysregulation, promoting neovascularization, and creating a microenvironment conducive to tumor growth ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al found six-snoRNA signatures (SNORA70B, SNORD12B, SNORD93, SNORA59B, SNORD116-2, and SNORA2) were superior indicators to routine clinical factors (AUC = 0.732) [ 44 ]. Li et al found that patients with low PIK3CA expression had poorer overall survival, and the AUC of their ROC curve was 0.775 [ 45 ]. Li et al found that the area under the curve (AUC) values of 1-year, 3-year and 5-year survival rates of the model constructed with seven cuproptosis-related genes were 0.814, 0.762 and 0.825, respectively [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Except for genes mutated across a large number of patients, some key genes in tumor initiation and progression are observed to be mutated in only a few patients [24]. For example, PIK3CA, which has been validated to be a ccRCC risk gene by previous studies [25][26][27], is mutated in no more than 5% of ccRCC patients [27]. It is difficult for purely frequency-based approaches to identify these genes with low mutation frequency but high risk.…”
Section: Introductionmentioning
confidence: 99%